Adoption, accommodation or opposition? - regional powers respond to American-led Indo-Pacific strategy. Issue 3 (20th May 2022) - Wilkins, Thomas; Kim, Jiye
Abstract: This article examines the new prominence accorded to the "Indo-Pacific" (IP) concept in the strategic narratives championed by the US and its closest allies, (Japan and Australia), and then juxtaposes this with the responses of other key regional powers. To this purpose, Part I distils a concise conceptual model encompassing three interlocking facets – mental maps, political/ideological drivers, and visions of regional order – designed to structure the following empirical analyses. Part II then accesses this model to reveal how these facets are reflected in the discursive and policy-making practices of the US and its close allies, as embodied in their (combined) regional strategies. Next, Part III considers how a cross-section of major states in the region – India, South Korea, and China - have responded to this enterprise, to determine the degree to which they have adopted, accommodated or opposed the IP concept, or otherwise propose national alternatives to the US-centered project. It concludes that the IP concept is not simply an objective geopolitical descriptor, but rather a controversial and contested discursive field, subject to multiple interpretations. Such a polarizing concept will likely contribute to further sharpening of strategic mistrust and geopolitical competition amongst the region's major powers.